In Vitro Assembly Kinetics of Cytoplasmic Intermediate Filaments: A Correlative Monte Carlo Simulation Study - Muecke, Norbert; Winheim, Stefan; Merlitz, Holger; Buchholz, Jan; Langowski, Joerg; Herrmann, Harald (PLoS ONE, 2016)
Intermediate filament (IF) elongation proceeds via full-width "mini-filaments", referred to as "unit-length" filaments (ULFs), which instantaneously form by lateral association of extended coiled-coil complexes after assembly is initiated. In a comparatively much slower process, ULFs longitudinally interact end-to-end with other ULFs to form short filaments, which further anneal with ULFs and with each other to increasingly longer filaments. This assembly concept was derived from time-lapse electron and atomic force microscopy data. We previously have quantitatively verified this concept through the generation of time-dependent filament length-profiles and an analytical model that describes assembly kinetics well for about the first ten minutes. In this time frame, filaments are shorter than one persistence length, i.e. 1 ?m, and thus filaments were treated as stiff rods associating via their ends. However, when filaments grow several ?m in length over hours, their flexibility becomes a significant factor for the kinetics of the longitudinal annealing process. Incorporating now additional filament length distributions that we have recorded after extended assembly times by total internal reflection fluorescence microscopy (TIRFM), we developed a Monte Carlo simulation procedure that accurately describes the underlying assembly kinetics for large time scales.
EVALuna2:7351